Beta EEG reflects sensory processing in active wakefulness and homeostatic sleep drive in quiet wakefulness. (30th January 2016) - Grønli, Janne; Rempe, Michael J.; Clegern, William C.; Schmidt, Michelle; Wisor, Jonathan P.
Summary: Markers of sleep drive (<10 Hz; slow‐wave activity and theta) have been identified in the course of slow‐wave sleep and wakefulness. So far, higher frequencies in the waking electroencephalogram have not been examined thoroughly as a function of sleep drive. Here, electroencephalogram dynamics were measured in epochs of active wake (wake characterized by high muscle tone) or quiet wake (wake characterized by low muscle tone). It was hypothesized that the higher beta oscillations (15–35 Hz, measured by local field potential and electroencephalography) represent fundamentally different processes in active wake and quiet wake. In active wake, sensory stimulation elevated beta activity in parallel with gamma (80–90 Hz) activity, indicative of cognitive processing. In quiet wake, beta activity paralleled slow‐wave activity (1–4 Hz) and theta (5–8 Hz) in tracking sleep need. Cerebral lactate concentration, a measure of cerebral glucose utilization, increased during active wake whereas it declined during quiet wake. Mathematical modelling of state‐dependent dynamics of cortical lactate concentration was more precisely predictive when quiet wake and active wake were included as two distinct substates rather than a uniform state of wakefulness. The extent to which lactate concentration declined in quiet wake and increased in active wake was proportionate to the amount of beta activity. These data distinguish quiet wake from active wake. Quiet wake, particularly when characterized by beta activity, is permissive to metabolic and electrophysiological changes that occur in slow‐wave sleep. These data urge further studies on state‐dependent beta oscillations across species.